182 QUALITY IMPROVEMENT OF THE REFERRAL SYSTEM TO EDITH (EMERGENCY DEPARTMENT IN THE HOME) SERVICE. (18th November 2021) - Prendergast, C; McNamara, R
Abstract: Background: Our department has been providing an Emergency Department in the Home (EDITH) service since early 2020. The goal is to bring the emergency services to older people and prevent unnecessary attendances to the ED. With over 3, 000 patients seen in its first 14 months, this heavily used service needs a proficient and safe referral system. The previous referral system predominately involved handwritten referrals and phone calls. Our aim was to streamline this via the introduction of the Siilo Application as a solitary referral source. A referral proforma was also drawn up to ensure all relevant details were included. Methods: A baseline survey was conducted to establish staff's opinion on the initial referral system. The questions were. 1. Are you happy with the current system of referring patients to EDITH? 2. Do you think that some referrals are being missed or delayed secondary to the current system? 3. Rank your current satisfaction with the referral system out of ten? There was also an area for feedback in the survey. The new system was then introduced using the Siilo Application. Staff were trained in its use and a referral proforma was put in place. After three months of use a second survey was conducted with the same questions. Results: 60% were happy with the new referral system, up from 11% on the first survey. Those who believed referrals were being missed had fallen from 88.9% to 70%. The average score out of ten for the current system was 6.9, improved from 5.7. Conclusion: Having a safe, user friendly and efficient referral system for complex patients is a fundamental part on the service we provide. Staff satisfaction with the referral system, especially in an emergency setting, is paramount to ensure adequate and safe referrals. Satisfaction rates did improve with the introduction of the Siilo Application, but there is room for further improvement.